The Erythrocyte (IntechOpen, 2023)
The Erythrocyte - A Unique Cell emphasizes the characteristic functions of erythrocytes and their vital role in metabolism, and their response to various situations. These changes can be used as diagnostic markers. This book gives insights into the key features of erythrocyte survival in the oxidizing environment and their functional aspects. It also examines the interactions and responses of erythrocytes with other cells and their role as messengers and potential indicators during disease conditions. Furthermore, the book discusses hormonal effects on erythrocyte functions, the major role of reticulocytes as markers, and the blood disorder- ?-thalassemia, its pathophysiology, underlying factors, and different treatments. Finally, the book examines the unique and crucial characteristic of erythrocyte deformability and its significance as a diagnostic tool for congenital defects.